Noticings with instructional implications in post‐licence driver training. (21st February 2018) - Rauniomaa, Mirka; Lehtonen, Esko; Summala, Heikki
Abstract : Drawing on ethnomethodology and conversation analysis, the study examines video data in which drivers with a valid licence participate in voluntary instructor‐led training. The study discusses noticings by the instructor that concern current events or states of affairs and prompt the driver to adjust her driving or that concern habitual practices developed by the driver over time and encourage her to alter them in the future. The former are simple noticings, whereas the latter are prefaced with "I notice that." The design and timing of the noticings reveal how they are to be understood with respect to the mobile instructional situation. Moreover, they make visible the instructor's ongoing monitoring and assessment of the driver's performance and the instructor's expectations regarding the driver's experience and competence.